History of the Salajiqoh Dynasty - Abdul Gofur (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
In North America The Salajiqoh dynasty originates from the Salajiqoh dynasty, also known as the Salajiqoh dynasty, is one of the dynasties that played an important role in the history of the Middle East and Central Asia in the Middle Ages. The Salajiqoh dynasty was founded by a group of Turkic peoples led by Tughril Beg in the early 11th century. In the Salajiqoh dynasty there were systemic devices that formed an integral unit and wholeness in a system of state government. This research includes the type of library research or library research. Literature research is a type of research based on the analysis and interpretation of data taken from written sources, such as books, journal articles, reports, papers, and other sources available in written form. The Salajiqoh dynasty was the first Turkish Islamic empire to rule the Islamic world. The power he held was so broad that it covered Central Asia and the Middle East – stretching from Anatolia to Punjab in southern Asia. The Great Salajiqoh Empire, which began to take power in the 11th to 14th centuries, was founded by the Turkic Oghuz tribe who embraced Islam. These devices constitute and form an integral unit and integrity in a system of state government including viziers, qadi, tax officials, close friends, intelligence, military. Science began to develop and progress during the reign of Maliksyah and his prime minister, Nizam al-Mulk. It was Nizam al-Mulk who initiated the establishment of the Nizamiyah (1065 AD) Madrasa (University) and the Hanafiyah Madrasa in Baghdad.